ANALISIS HUKUM TINDAK PIDANA KORUPSI DANA HIBAH PILKADA BUPATI DAN WAKIL BUPATI SERDANG BEDAGAI TAHUN 2020 STUDI PUTUSAN NOMOR: 96/PID.SUS-TPK/202I/PN.MDN - Sihotang, Tumpak Mangasi; Eddy, Triono (JURNAL DOKTRIN REVIEW, 2023)
Funding for Regent and Deputy Regent election activities is borne by the Regency APBD based on Minister of Home Affairs Regulation No: 41 of 2020 concerning Funding for Governor, Regent and Mayor election activities sourced from the Regional Revenue and Expenditure Budget. In Article 2 paragraph (2). With regard to the role of the KPU Secretariat, there is an opportunity for criminal acts of corruption to occur by the KPU Secretariat because the KPU Secretary indirectly serves as KPA, the authority as KPA in Article 8 PP No: 45 of 2013. Corruption crimes in the form of grant funds for the Regional Election of Regent and Deputy Regent in Medium Bedagai Regency in the 2020 election, with the Defendant having been investigated with Decision No:96/Pid.Sus-TPK/202I/PN.Mdn. Normative legal research methods. The results of the research are the application of criminal law in cases of corruption in grant funds for the Regional Election of Regent and Deputy Regent, by means of efforts to enforce criminal law by the Prosecutor by transferring it to the Corruption Court so that legal certainty of benefit and justice can be realized, and the judge's consideration has fulfilled all the elements, the Defendant is proven legally and convincingly guilty of committing criminal acts of corruption together. So, as a suggestion, in preparing the Regional Grant Agreement Text regarding the implementation of grant funds for the election of Regent and Deputy Regent, Law Enforcers should be involved; and so that there are no deviations in the use of authority; Then there should be special regulations made by the Indonesian KPU, so that the Work Units in each KPU at the regional level are not involved in abusing their authority.